Detection of soil and groundwater domestic pollution by the electrical resistivity method in the West Bank, Palestine. Issue 4 (1st January 2012) - Sirhan, Asal; Hamidi, Mohammad
ABSTRACT: The environmental assessment of domestic pollution is required to minimize the risk of soil and groundwater contamination. Septic storages (localized sources) may affect the surrounding soil and permeable chalky formations by the intrusion of waste water within the formations. The aim was to develop a clearer understanding of waste water leakage due to numerous waste septic storages implemented within chalk formations at different towns and villages in the West Bank, Palestine. The possession of such information may be used to maintain not only sustainable development but also the protection of the environment. Since waste water is a good electrical conductor, the Electrical Resistivity Tomography (ERT) technique was employed for its ability in determining lateral and vertical electrical resistivity variations of possible infiltration zones of waste water. Furthermore, extracted vertical electrical soundings (VES) provide indications about the nature of the geological features that can affect the behaviour of leakage. Geo‐electrical surveys were carried out to investigate their utility in detecting and examining the effect of pollution. The two‐dimensional (2D) inverted models obtained by many electrode array configurations; Schlumberger, Wenner and dipole‐dipole were consistent. Interpretation of Direct Current (DC) geoelectrical resistivity field data demonstrates the existence of low‐apparent electrical resistivity ρ a zones ( ρ a < 15 Ω ·m). A trend of decreasing resistivity is observed towards the horizontal direction of the existing storages, indicating the location of pollution plumes in soil and chalky formations. In addition, the heterogeneity of the shallow subsurface can be considered as the main reason for the fluids infiltration. The relative percentage of the resistivity Δ ρ % is well documented, the Δ ρ % value is minimized as a significant difference appears i.e., the relative percentage reaches ‐82% at the upper surface and it reaches to ‐44% where the septic tanks are located. These reliable results are considered as a key role in monitoring the environmental impacts of waste water on a groundwater system and high‐conductivity zones. Therefore, further geophysical prospecting projects for environmental issues can be realized by this technique.